Use of Fertigation and Municipal Solid Waste Compost for Greenhouse Pepper Cultivation - Tzortzakis, Nikos G.; Gouma, Sofia; Dagianta, Eleni; Saridakis, Christos; Papamichalaki, Maria; Goumas, Dimitrios E.; Manios, Thrassyvoulos (My University, 2012)
Municipal solid waste compost (MSWC) and/or fertigation used in greenhouse pepper (Capsicum annuum L.) cultivation with five different substrates with soil (S) and/or MSWC mixtures (0-5-10-20-40%) used with or without fertigation. Plants growth increased in 10-20% MSWC and fertigation enhanced mainly the plant height. Fruit number increased in S : MSWC 80 : 20 without fertilizer. Plant biomass increased as MSWC content increased. There were no differences regarding leaf fluoresces and plant yield. The addition of MSWC increased nutritive value (N, K, P, organic matter) of the substrate resulting in increased EC. Fruit fresh weight decreased (up to 31%) as plants grown in higher MSWC content. Fruit size fluctuated when different MSWC content used into the soil and the effects were mainly in fruit diameter rather than in fruit length. Interestingly, the scale of marketable fruits reduced as MSWC content increased into the substrate but addition of fertilizer reversed this trend and maintained the fruit marketability. MSWC affected quality parameters and reduced fruit acidity, total phenols but increased fruit lightness. No differences observed in fruit dry matter content, fruit firmness, green colour, total soluble sugars and EC of peppers and bacteria (total coliform and E. coli) units. Low content of MSWC improved plant growth and maintained fruit fresh weight for greenhouse pepper without affecting plant yield, while fertigation acted beneficially.
Keywords: Growing media; Peat; Growing medium